Evaluating the Necessity of Screw Replacement in Sacral Bone Loosening: A Minimally Invasive Approach for Treatment with Local Anesthesia - Baloglu, Murat; Millet, Hakan; Ercan, Serdar (Indian Journal of Neurosurgery, 2023)
This study aimed to investigate a minimally invasive approach to address the issue of bone loosening in patients who have undergone posterior spinal fusion surgery. If left untreated, sacral bone loosening can result in nerve damage, reduced mobility, and chronic pain. The standard surgical treatment involves replacing the loosened screw with a larger one, requiring significant surgical intervention and complete instrument disassembly. The use of polymethylmethacrylate (PMMA) to increase the strength of the vertebral body was also described, but the results were contradictory. We aim to evaluate the efficacy of filling just only the gap between bone and screw instead of the vertebral body.This study included patients who had undergone posterior transpedicular stabilization but showed signs of sacral bone loosening in follow-up. The gap between the screw and the bone was targeted instead of the vertebral body and filled using PMMA. The procedure was performed under local anesthesia and fluoroscopy, and the preoperative and postoperative visual analog scale (VAS) scores were compared at 1, 3, and 12 months after the procedure.The study included 17 patients who underwent 28 procedures, with 11 patients receiving bilateral and 6 receiving unilateral approaches. The results showed a significant decrease in postoperative VAS scores compared to the preoperative scores, indicating reduced pain and discomfort. PMMA, as a bone filler, has been reported to provide good stability and support to the bone-implant interface, thereby reducing the risk of screw loosening and improving the outcome of spinal fusion surgery.In conclusion, the study demonstrates the efficacy of a minimally invasive approach using PMMA to treat sacral bone loosening in patients who have undergone posterior spinal fusion surgery. The procedure is safe, minimally invasive, and provides significant pain relief, making it a viable alternative to traditional surgical methods.
Keywords: bone loosening; screw loosening; polymethylmethacrylate; fusion insufficiency